Protective effect of Zataria multiflora Boiss against sodium nitrite-induced hepatotoxicity in rats - Fateme Ahmadi; Ali Louei Monfared; Neamatollah Shakarami (Mashhad University of Medical Sciences, 2022)
Objective: Sodium nitrite (NaNO2) is used as a color stabilizer and antimicrobial agent in preservation of cured meat and fish. However, extensive use of this agent in the meat industries increased worries about its detrimental effects on human health. Zataria multiflora (Z. multiflora) is a well-known plant with therapeutic properties in the traditional medicine. Therefore, the present study was conducted to investigate the protective effect of this plant against sodium nitrite-induced hepatotoxicity.Materials and methods: Thirty-two male Wistar rats were divided into 4 groups: Control (without any treatment), nitrite (350 mg/kg by gavage for 60 days), NaNO2 plus Z. multiflora (rats treated with NaNO2 350 mg/kg gavage for 60 days and simultaneously received Z. multiflora extract at 200 mg/kg, ip) and Z. multiflora group (rats treated with Z. multiflora extract at 200 mg/kg, ip). At the end of the study, rats were euthanized and liver tissue samples were taken and studied under microscopy. Also, serum levels of liver function enzymes and antioxidant defense systems were measured. The results were analyzed using SPSS software and a p<0.0.5 was considered significant.Results: Results showed that NaNO2 induces liver injuries and altered hepatic histo-architecture. Also, NaNO2 significantly altered the biochemical profiles and antioxidant defense parameters of the liver. However, treatment with Z. multiflora improved tissue integrity as well as antioxidant defense status and biochemical conditions of the liver.Conclusion: Administration of Z. multiflora extract has beneficial effects on the NaNO2-induced histological and functional toxicity in the liver.